Studi Komparasi Hasil Belajar Pada Pembelajaran Tematik Model Discovery Learning dan Probelm Based Learning Siswa Kelas V Gugus V Kota Bengkulu - Reza Meta Nela; Dalifa (JURIDIKDAS, 2023)
This study aims to determine the differences in learning result in thematic lessons using models of Discovery Learning and Problem Based Learning (PBL) fifth grade students of Elementary School Cluster V of Bengkulu City. The research method used was Quasi Experimental with a type of PretestPosttest Comparison Group research design. The study population was all fifth grade students of Elementary School Group V of Bengkulu City. The research sample was fifth grade B at SDN 02 for experimental class 1 and fifth grade A student at SDN 09 for experimental class 2. The sampling technique used purposive sampling. The research instrument using tests of cognitive learning result multiple choice questions was given through pretest and posttest. Learning result for attitudes and skills using observation sheet instruments and using simple descriptive analysis to calculate the percentage of each descriptor. Based on the results of data analysis obtained (1) the highest attitude aspect is the aspect that uses the Discovery Learning model, namely the attitude of curiosity while the highest attitude for the Problem Based Learning model is also an attitude of curiosity (2) the highest learning result of the skill aspects for the Discovery Learning model are the skills of item B while the highest attitude for the Problem Based Learning model is the skill item C. (3) H0 is accepted so that there is no significant difference between students using discovery learning models and problem based learning models.